Severe myelinopathy in 49,XXXXY syndrome - Buller, Mark A (Neuroradiol J, 2017)
49,XXXXY is a rare aneuploidy with neuroanatomic findings scarcely reported in the literature. Given the fact that many of its phenotypic characteristics are similar to Klinefelter patients, 49,XXXXY has been treated as a variant of Klinefelter syndrome in the past. Newer studies have shown that intellectual disabilities and cardiac sequelae are more common in 49,XXXXY making the need for more precise characterization of the disorder essential. Prior case studies have demonstrated focal (and to a lesser extent confluent) white abnormalities as well as enlarged perivascular cysts (often in clustered arrangements) in the brains of these patients, but high resolution magnetic resonance images of severe myelinopathy are infrequently documented. Presented here is an exceptional manifestation of this rare disease with substantial findings in the brain exhibiting both confluent white matter changes and diffuse perivascular cysts. Cases such as this one serve to expand the differential considerations for confluent dysmyelinating disease and improve diagnostic efficacy.